Designing dual‐mode luminescence in Er3+ doped Y2WO6 microparticles for anticounterfeiting and temperature measurement. Issue 2 (8th October 2021) - Luo, Yurong; Zhang, Libin; Liu, Yuan; Heydari, Esmaeil; Chen, Liang; Bai, Gongxun
Abstract: In recent years, rare earth ions doped optical materials have been extensively utilized in anticounterfeiting, temperature measurement, and other fields. However, it is difficult for single‐mode photoluminescence to meet the increasingly complex anticounterfeiting needs in practice. In this article, Yb 3+ /Er 3+ codoped Y2 WO6 multifunctional microparticles have been designed and prepared, which can emit multimode luminescence and are used for anticounterfeiting and temperature measurement. Under excitation at 254, 365, and 980 nm, Y2 WO6 :Yb 3+ /Er 3+ microparticles can emit blue, green, and yellow‐green luminescence, respectively. The multicolor emission is helpful to improve the security of anticounterfeiting in multimode. In addition, the upconversion, downconversion luminescence, and downconversion lifetime attenuation of this material can be used for fast responsive and noncontact temperature measurement. Among the three temperature measurement methods, the material has the highest sensitivity under the downconversion temperature measurement method, which is 1.25 × 10 –2 K –1 (at 303 K). The results suggest that the Y2 WO6 :Yb 3+ /Er 3+ microparticles have excellent applications in the domain of multimode anticounterfeiting and temperature measurement.